Modeling multifunctionality of agriculture at a farm-level: The case of kerkini district, Northern Greece - Vassalos, Michael; Dillon, Carl R.; Freshwater, David; Karanikolas, Pavlos (Applied Studies in Agribusiness and Commerce, 2010)
Multifuncionality has become a central concern at both conceptual and empirical levels. In this study, a comparative evaluation of the economic performance of conventional and multifunctional farms (mainly organic farms) was conducted for the Lake Kerkini region (North Greece) with the use of mixed integer non-linear programming method. The economic performance of farms was evaluated in terms of farm income, resource allocation, production level and production mix. The results indicate that multifunctional farms have overall better economic performance and young farm managers are keener to adopt multifunctional farming than the older ones. Differences between the model results and the observed facts are attributed to the structural characteristics of the farms, along with the CAP measures and the existence of multiple objectives, beyond maximization of net farm returns.